2017
DOI: 10.1093/fampra/cmx127
|View full text |Cite
|
Sign up to set email alerts
|

German healthcare professionals’ perspective on implementing recommendations about polypharmacy in general practice: a qualitative study

Abstract: While many interventions to improve polypharmacy focus on the provision of pharmacological knowledge, a much wider range of domains need to be addressed, such as communication skills, patient involvement and practice organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 28 publications
1
36
1
Order By: Relevance
“…In contrast to Straßner et al [ 31 ], we found that on the individual level, physicians consider pharmacological information an essential dimension in the prescribing process in polypharmacy. They expect the digital availability of pharmacological knowledge to simplify decision-making.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to Straßner et al [ 31 ], we found that on the individual level, physicians consider pharmacological information an essential dimension in the prescribing process in polypharmacy. They expect the digital availability of pharmacological knowledge to simplify decision-making.…”
Section: Discussioncontrasting
confidence: 99%
“…This is consistent with prior studies that show that factors such as cohesion, trust and support predict organizational readiness for change and implementation success . INSN providers also share a desire for ongoing interdisciplinary communication related to NHF, a desire reported in a variety of settings throughout the world . Our study emphasises that collaboration is a key element prior to implementation and essential for change in an organization.…”
Section: Discussionsupporting
confidence: 89%
“…Determinant frameworks, specifically, are used to identify barriers and enablers of implementation [40]. To date, a number of empirical studies used the TICD and other theoretical frameworks to explore implementation issues across therapeutic areas, including lower back pain [41,42], hand hygiene [43], blood transfusion [44], medication prescribing [45], laboratory testing [46], polypharmacy [47], evidence-based recommendations for chronic conditions [48] and primary care [49], schizophrenia [50] and dementia [51]. In general, uncertainty about how to choose interventions that best match implementation determinants in a given context have been reported [52].…”
Section: Discussionmentioning
confidence: 99%